Menjadi Orang Tua Cerdas di Era Digital: Membangun Generasi Tangguh Melalui Sosialisasi Pengasuhan Anak - Shofiah, Nurul; Falqahi A, Rasya; Qodariaha, Aulia; Sukma, Adie (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2024)
Nowadays, humans are living in the digital age, undergoing incredible technological advances. Humans can't live without technology. Technology is everything for humans, so its positive and negative impact on humans goes hand in hand. The negative impact perceived on the sophistication of today's digital age is very evident, like the moral behavior of a child that is quite worrying. Therefore, the role of the parent's pattern of care in the family environment largely determines the values the child acquires. This socialization activity aims to improve the quality of parental care patterns in order to build a positive character in children especially in this digital age. The results of this socialization activities include participants becoming more aware of the importance of parent support when children access digital media, participants get tips and strategies to build family commitment in the use of digital technology, and there is an increase in the knowledge of the participants about the pattern of child care in the digital era. Parents are expected to be able to implement the tips and strategies acquired to build a sturdy generation